Castilian and Portuguese merchants in collaboration (1580-1590). Has the Hispanic Monarchy favored Iberian commercial partnerships? - Ribeiro, Ana Sofia (2015)
The Iberian Union allowed the existence of formal mechanisms of government authority in Portugal. In what concerns the Iberian trade dynamics, including the colonial circuits, the Habsburgs legislated according to those that would be the most politically convenient circumstances, making an impact on Iberian affairs. Over the last decade, historical literature has highlighted the transnational nature of Early Modern business partnerships. On the other hand, Iberian scholars have put forward many case studies that show formal or informal Portuguese participations in the Spanish Indies affairs. However, the inverse situation as not been considered yet. What was the role played by Castilian merchants in the Portuguese colonial trade? This paper aims to present data about the collaboration between Portuguese and Castilian merchants within the European and the overseas trade dynamics, approaching the Iberian Union as an event that favored these business partnerships. It also debates the formal or informal nature of these relationships. Were they promoted by the State’s policies or, alternatively, were they devised as a means to bypass the Crown’s monopolistic policies? For this propose, we will analyze Portuguese notarial records from the period between 1580 and 1590.